Praktik Tying Agreement oleh PT Astra Honda Motor terhadap Dugaan Praktik Persaingan Usaha Tidak Sehat (Lex Jurnalica, 2023)
The Commission for Business Competition Supervision (KPPU) is an independent institution established to oversee the implementation of Law No. 5/1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition which is stipulated through a Presidential Decree. As an institution authorized by Law No. 5/1999 to supervise business actors in carrying out their business activities so as not to carry out monopolistic practices and or unfair business competition, KPPU had decided the case regarding the alleged practice of a tying agreement carried out by PT Astra Honda Motor, as stated in the Decision of KPPU No. 31/KPPU-I/2019. This study aims to find out an overview of the practice of tying agreements based on Law No. 5/1999 and analyses the alleged practice of tying agreements carried out by PT Astra Honda Motor in the Decision of KPPU No. 31/KPPU-I/2019. This research was a descriptive and normative legal theory, which applied to statute and case approach. This study used the Law No. 5 of 1999 concerning The Ban on Monopolistic Practices and Unfair Business Competition and some of verdicts of KPPU as its primary legal source and literature, expertâ€™s opinions, as well as journals and study report as secondary law source. Data in this study were analysed using qualitative technique.Â Keywords: KPPU, tying agreement, business competition